Monitoring Pendeteksi Kebocoran Gas LPG Pintar Menggunakan Sensor MQ-6 dengan Telegram(Studi Kasus pada UMKM Kabupaten Kendal) - Fahrul Rahman; Sumaryanto Sumaryanto; Iman Saufik Suasana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The use of Liquefied Petroleum Gas (LPG) in household and culinary business activities has potential fire and explosion risks when gas leakage is not detected quickly. This study aims to develop a smart LPG leakage detection device based on the Internet of Things (IoT) using the MQ-6 sensor and Telegram notifications at Bakso Imadora Kaliwungu. This research employed the Research and Development (R&D) method through needs analysis, system design, prototype development, integration, testing, and validation. The system consists of an ESP32 Lolin 32 Lite, MQ-6 gas sensor, flame sensor, MG996R servo motor, LED, buzzer, step-down module, and Telegram Bot. The test results showed that the device was able to detect LPG leakage and fire in real time, activate local warnings, close the gas valve automatically, and send Telegram notifications to users. The system achieved 95.3% gas detection accuracy and 97.8% notification delivery success under stable Wi-Fi conditions. Product validation involving 10 respondents produced an average score of 3.46, which was categorized as good and close to very good. Therefore, the developed system is feasible to be used as a safety support device for culinary businesses that use LPG.